Anti-inflammatory Properties of Hibiscus Leaf Extracts: A Potential Therapeutic Agent for Post-immunization Fever in Infants - Riri Aprianti; Vitria Yenti (Archives of The Medicine and Case Reports, 2025)
Post-immunization fever is a common side effect in infants, often causing discomfort and concern for parents. Hibiscus leaf extracts have been traditionally used for their anti-inflammatory and antipyretic properties. This study investigated the efficacy of hibiscus leaf extracts as a potential therapeutic agent for post-immunization fever in infants. A randomized controlled trial was conducted with 120 infants aged 2-4 months who received their first dose of the diphtheria-tetanus-pertussis (DPT) vaccine. Participants were randomly assigned to either the hibiscus extract group (n=60) or the control group (n=60). The hibiscus extract group received a standardized dose of hibiscus leaf extract orally, while the control group received standard care. Fever was assessed at regular intervals for 48 hours post-immunization. Infants in the hibiscus extract group exhibited a significantly lower incidence of fever (p=0.02) and a reduced duration of fever (p=0.04) compared to the control group. Furthermore, the hibiscus extract group showed a lower average temperature throughout the observation period. No adverse effects were reported in the hibiscus extract group. In conclusion, hibiscus leaf extracts demonstrate promising anti-inflammatory properties and may serve as a safe and effective therapeutic agent for post-immunization fever in infants. Further research is warranted to explore the underlying mechanisms and long-term effects.